Parental Involvement on Children's Success: An Exploration of School Administration's Role from parental perspectives - Basnyat, Samjhana (Innovative Research Journal, 2025)
It is frequently acknowledged that parental involvement is an essential component in determining a child's academic success. School administrators show an essential role in encouragement of parental involvement in school activities, identifying that active participation enhances students' academic and social development. This study highlights how major stakeholders, such as teachers and school administrators, can promote parental involvement in their children's learning. The primary objective is to explore how school leaders and administrators may involve parents in the educational process. Furthermore, the study aims to identify the key factors which affect the involvement of parents and suggest practical recommendations to accomplish accordingly. The study was carried out at community schools in Kathmandu district using a general qualitative techniques that integrated observations and interviews to collect information from parents and school administrators. Assessing the level of parental involvement alongside looking at how school administrators perceive about fostering collaboration with community were the furthermost focus of the study. The results of the study show that views regarding school leadership and parental involvement are substantially interconnected. The study however, show a concerning absence of parental involvement in the educational process. Insufficient resources, cultural barriers and communication gaps are some of the elements that foster the existence of this concern. The study addresses the critical role that school administration performs in encouraging and promoting parental involvement with the goal to enhance students' academic performance. School administrators need to set a high priority on open discourse and cooperative efforts with parents in order to address the observed lack of parental involvement. In summary, parental involvement is a major predictor of children's academic success, and school administration's dynamic contribution is significant for enriched involvement of parents in children’s learning.